Engaging users using movie mobile advertising: technology acceptance and purchase intention - Abu Bakar, Mohd Syuhaidi; Bidin, Rosmiza (Canadian Center of Science and Education, 2014)
The study identified the relationships between technology acceptance and purchase intentions on movie mobile advertising among Twitter users in Malaysia. Technology Acceptance Model was used to predict the acceptance of computer-based technology based on technology use and usefulness. The objective of this study is to investigate the relationship between attitude (technology acceptance) towards movie mobile branding in Malaysia and purchase intention. Data was randomly collected from 400 Twitter users in Malaysia and analyzed with statistical analysis (SPSS) using descriptive and correlation analysis. The findings of this paper advocate that technology acceptance attitudes in movie mobile branding contributed significantly towards movie purchase intention in Malaysia. This paper introduces the contribution of attitudes in the study of branding communication utilizing mobile telecommunications technology in Malaysia.